Nitric oxide : a key mediator of biofilm dispersal with applications in infectious diseases - Barraud, Nicolas (2015)
Studies of the biofilm life cycle can identify novel targets and strategies for improving biofilm control measures. Of particular interest are dispersal events, where a subpopulation of cells is released from the biofilm community to search out and colonize new surfaces. Recently, the simple gas and ubiquitous biological signaling molecule nitric oxide (NO) was identified as a key mediator of biofilm dispersal conserved across microbial species. Here, we review the role and mechanisms of NO mediating dispersal in bacterial biofilms, and its potential for novel therapeutics. In contrast to previous attempts using high dose NO aimed at killing pathogens, the use of low, non-toxic NO signals (picomolar to nanomolar range) to disperse biofilms represents an innovative and highly favourable approach to improve infectious disease treatments. Further, several NO-based technologies have been developed that offer a versatile range of solutions to control biofilms, including: (i) NO-generating compounds with short or long half-lives and safe or inert residues, (ii) novel compounds for the targeted delivery of NO to infectious biofilms during systemic treatments, and (iii) novel NO-releasing materials and surface coatings for the prevention and dispersal of biofilms. Overall the use of low levels of NO exploiting its signaling properties to induce dispersal represents an unprecedented and promising strategy for the control of biofilms in clinical and industrial contexts.